Service quality rendered by the public universities in central region of Malaysia / Faizatul Akmam Amirrudin, Raslina Mohamed Nor and Najah Lukman - Amirrudin, Faizatul Akmam; Mohamed Nor, Raslina; Lukman, Najah (2006)
Service quality is not a new issue in service industry but where the higher education institution in Malaysia is concerned, again the service quality is a pressing subject. With many players in the higher education institutions in Malaysia ranging from public universities to private colleges to branches of foreign universities, the competition among them is great. Nowadays, customers choose the institution, which can deliver more then what they expect. Therefore, quality plays the major important role to differentiate them from competitors and at the same time gain competitive advantage. There is a few research or study on the service quality of higher education in Malaysia. The institutions are not able to get to know what are the perceptions of the students towards the services provided by them. The institutions also are lack of knowledge on what the expectations of the students from them. The study main focus is to identify some differences of service quality from different public universities in Central Region of Malaysia. Theoretical framework was developed in relation to the objectives and the related literature review. Questionnaire was developed as the mode of data collection. A total of 630 questionnaires were distributed to the samples delivered directly to students from UM, UKM and UPM and 610 questionnaires were returned back to the researcher.